PENGEMBANGAN CHATBOT KONSULTASI KESEHATAN MENTAL KESEHATAN MENTAL BERBASIS OPEN AI MODEL GPT-3.5 TURBO MENGGUNAKAN MEDIA WHATSAPP (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This study aims to develop a WhatsApp-integrated chatbot utilizing OpenAI's GPT-3.5 Turbo model to assist in mental health contexts. Through this technological integration, the chatbot is capable of providing effective and empathetic responses to mental health-related inquiries and discussions. The methodology encompasses chatbot development, Black Box Testing, Usability Testing, and analysis of feedback from users and psychologists. The findings indicate that the chatbot successfully implements profound and relevant interactions in a mental health context. This chatbot offers an alternative approach to providing psychological support and mental health information. The study opens avenues for further development in the field of mental health chatbots, particularly in integrating the latest AI technology.